JASAD ANAK BUAH KAPAL DAN KONSEP KETENAGAKERJAAN DI INDONESIA - Trie Rahmi Gettari; Yudha Prasetyanov; Khairani Khairani (Ensiklopedia of Journal, 2023)
A fisherman is a seafarer because "seafarer means any person who is employed or engaged or works in any capacity on board a ship to which this Convention applies"  defined in Indonesian is "seafarer means any person employed or involved or working in any capacity on board a ship where this law applies", so that fishermen can also be referred to as seafarers. The affidavit also notes that consent from both parents has been obtained, and the contract will not cause legal problems or involve the police in Indonesia. This statement letter is made voluntarily in good health without any coercion from any party, and is considered valid after being signed on a stamp in accordance with applicable law in Indonesia. But it is also not uncommon for an agreement to be included in the work contract of the crew because of limited space on the ship to accommodate the body. However, it is important to dig deeper and examine the position of the confinement clause in the ABK employment contract.Keywords: Crew, Corpse, Confinement.